Roles of the Neuron-Restrictive Silencer Factor in the Pathophysiological Process of the Central Nervous System - Su, Xin-Jin; Shen, Bei-Duo; Wang, Kun; Song, Qing-Xin; Yang, Xue; Wu, De-Sheng; Shen, Hong-Xing; Zhu, Chao (Frontiers in Cell and Developmental Biology, 2022)
The neuron-restrictive silencer factor (NRSF), also known as repressor element 1 (RE-1) silencing transcription factor (REST) or X2 box repressor (XBR), is a zinc finger transcription factor that is widely expressed in neuronal and non-neuronal cells. It’s a master regulator of the nervous system, and the function of NRSF is the basis of neuronal differentiation, diversity, plasticity, and survival. NRSF can bind to the neuron-restrictive silencer element (NRSE), recruit some co-repressors, and then inhibit transcription of NRSE downstream genes through epigenetic mechanisms. In neurogenesis, NRSF functions not only as a transcriptional silencer that can mediate the transcriptional inhibition of neuron-specific genes in non-neuronal cells and thus give neuron cells specificity, but also as a transcriptional activator to induce neuronal differentiation. Many studies have confirmed the association between NRSF and brain disorders, such as brain injury and neurodegenerative diseases. Overexpression, underexpression, or mutation may lead to neurological disorders. In tumorigenesis, NRSF functions as an oncogene in neuronal tumors, such as neuroblastomas, medulloblastomas, and pheochromocytomas, stimulating their proliferation, which results in poor prognosis. Additionally, NRSF-mediated selective targets gene repression plays an important role in the development and maintenance of neuropathic pain caused by nerve injury, cancer, and diabetes. At present, several compounds that target NRSF or its co-repressors, such as REST-VP16 and X5050, have been shown to be clinically effective against many brain diseases, such as seizures, implying that NRSF and its co-repressors may be potential and promising therapeutic targets for neural disorders. In the present review, we introduced the biological characteristics of NRSF; reviewed the progress to date in understanding the roles of NRSF in the pathophysiological processes of the nervous system, such as neurogenesis, brain disorders, neural tumorigenesis, and neuropathic pain; and suggested new therapeutic approaches to such brain diseases.